Reliability of a commercially available threshold loading device in healthy subjects and in patients with chronic obstructive pulmonary disease. Issue 6 (June 1996) - Gosselink, R; Wagenaar, R C; Decramer, M
Abstract : BACKGROUND: Threshold loading with the Nickerson and Keens' device is frequently applied in the training and assessment of inspiratory muscles. However, this equipment is not easily applied in clinical practice and training. A study was therefore designed to investigate the accuracy and reliability of the Threshold, a commercially available threshold loading device. METHODS: The resolution (accuracy) of the system was determined by measuring variation of pressure and flow during one minute in an experimental setup. The reproducibility and flow independence were then determined during threshold loading at six different inspiratory loads between 25% and 50% maximal inspiratory pressure (PImax) in 10 patients with chronic obstructive pulmonary disease (COPD) and eight healthy subjects. RESULTS: In the first experiment the mean variation of the sustained pressure for all loads was 1.7%. The mean coefficients of variation for pressure and flow measurements were 0.2% and 3%, respectively. In the second experiment the healthy subjects showed mean coefficients of variation for pressure and flow of 0.8% and 20.5%, respectively, and the patients showed mean coefficients of variation of 0.6% and 14.5%, respectively. CONCLUSIONS: During the in vitro experiment as well as during the experiments in patients with COPD and in healthy subjects only small variations in pressure were observed despite large variations in flow. The Threshold is a reliable and reproducible device for loading inspiratory muscles in patients with COPD as well as in healthy subjects.